Large-scale duplicate image retrieval technical research for the internet - Shu-peng WANG; Ming CHEN; Guang-jun WU (Tongxin xuebao)
For the typical social media application on the internet,a large-scale distributed duplicate image retrieval ap-proach based on random projection and the block DCT coefficients was proposed.On the basis of Hadoop,this approach exploited image signatures generated by random projection mapping to retrieve HBase efficiently.And candidate images with high-recall were achieved.Then in order to improve the retrieval precision,the block DCT coefficients were used to further filter candidate images.For 12 million images,experimental results showed that with our approach the recall ratio reached 98%,the precision ratio reached 93.2%,and the average retrieval time was 6.7s when H=2 and T=150.